2007
DOI: 10.1038/oby.2007.255
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Scientific Experts on Obesity: Implications for Awareness and Behavior Change

Abstract: BLEICH, SARA, ROBERT BLENDON, AND ALYCE ADAMS. Trust in scientific experts on obesity: implications for awareness and behavior change. Obesity. 2007;15: 2145-2156. Objective: To explore the relationship between public trust in scientific experts on obesity and public attention to nutrition recommendations, to investigate trust as a predictor of weight-related behaviors, and to identify the sociodemographic characteristics associated with high and low trust in scientific experts on obesity. Research Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
2
33
0
5
Order By: Relevance
“…Although scientific communicators may stress persuasion, deliberation would be better (39). Communicating uncertainty is essential to building credibility (40,41), and trust best predicts attention to scientific experts (42).…”
Section: Climate Scientists' Presumed Agendasmentioning
confidence: 99%
“…Although scientific communicators may stress persuasion, deliberation would be better (39). Communicating uncertainty is essential to building credibility (40,41), and trust best predicts attention to scientific experts (42).…”
Section: Climate Scientists' Presumed Agendasmentioning
confidence: 99%
“…96 For example, data suggest that Latinos with low educational attainment are more likely to distrust scientific experts on obesity. 97 Trust and credibility are critical when delivering information on health risks, especially on controversial and sensitive topics such as childhood overweight and obesity. 19 Science is an evolving process and at times seems contradictory.…”
Section: S54mentioning
confidence: 99%
“…The lack of trust in government has also been reported (17) . Previous findings have also reported women and those with higher education levels have more trust in scientific experts (12) . While neither of these continuous variables was related to trust of food per se, it is interesting that those who do not eat enough vegetables have a significantly higher level of trust of the broad community spectrum of society (from family to the medical system to broad levels of government) indicating, perhaps, a willingness to accept these bodies as authoritarian.…”
Section: Discussionmentioning
confidence: 77%
“…Another prerequisite for trust is that the health promotion message/campaign is correct and from reputable organisations (15) . A level of trust in the credibility of the message and in the organisation promoting the message is required before individuals contemplate changing their behaviour appropriately (12,16,17) ; as Hansen et al (18) suggested, if people do not 'trust the messenger, they will not trust the message' (p. 15). Studies from Europe suggest that trust in the media, farmers, politicians and the food industry has diminished in the face of well-publicised food scares, with consumers more likely to trust information about healthy eating received from medical practitioners and consumer groups than information received through the media (19,20) .…”
mentioning
confidence: 99%